Super-coarse hard alloy as well as preparation method and application thereof
By using the combination of continuously distributed ultracoarse WC powder and mediumcoarse WC powder in the rotary cutting teeth, the crystal grains of the cobalt bonding phase are refined, and the rotary cutting teeth in the hard rock and dry pore process in the prior art is solved. The problem of insufficient wear resistance in the case has achieved higher wear resistance and toughness, and improved the working efficiency of the rotary drilling rig.
Patent Information
- Application Number
- CN202411407224.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2025-02-18
AI Technical Summary
The existing rotary digging teeth face problems of insufficient wear resistance and high-temperature plastic deformation under hard rock, dry hole and complex rotary digging conditions, especially in hard rock rotary digging and dry hole rotary digging conditions above f10.
The continuous distribution of ultra-coarse WC powder is used in conjunction with medium-coarse WC powder. Through ball milling and spray-drying granulation, the grains of the cobalt bonded phase are refined, and the thickness of the cobalt layer at the WC/WC junction is increased, thereby increasing the alloy. strength and wear resistance.
It significantly improves the wear resistance and toughness of the rotary cutting teeth, reduces the consumption of the tooth in hard rock and dry hole conditions, and improves the working efficiency of the rotary cutting rig and the service life of the equipment.
Smart Images

Figure CN119464876A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of cemented carbide, and in particular relates to an ultra-coarse cemented carbide and a preparation method and application thereof. Background Art
[0002] The rotary drilling rig is a highly efficient and versatile construction machine, especially suitable for drilling operations in building foundation projects. It has many advantages: large installed power, strong output torque, large axial pressure, high mobility, high construction efficiency, and can be used in conjunction with a variety of drilling tools to adapt to a variety of drilling conditions such as short spirals, rotary buckets and rock formations. In dry and hard clay, dry rotary drilling methods without the need for stabilizing liquid wall protection can be used; while ordinary covering layers mostly use wet rotary drilling methods with static mud wall protection. Rotary drilling rigs have been widely used in bored pile projects for foundations such as bridges, municipal construction, and high-rise buildings.
[0003] Among the various drilling tools of rotary drilling rigs, pick-barrel drill bits are particularly suitable for hard rock rotary drilling and are the most widely used in domestic rock construction. The characteristic of pick-barrel drill bits is that a circle of picks is embedded in the cutting part of the lower part of the barrel. These picks are divided into three groups: inner cutting teeth, annular cutting teeth, and outer cutting teeth, which are staggered to improve cutting efficiency. During the rotary cutting process, the barrel drill cuts annular grooves on the rock. As the cutting depth increases, the core is twisted off at a 45° angle to the axis. In order to ensure smooth twisting and removal of the core, the height of the barrel of the barrel drill is designed to be greater than the diameter of the core.
[0004] The tensile strength and shear strength of rock are usually much lower than its compressive strength. This feature provides conditions for efficient rock drilling and helps save energy. When drilling into brittle rock formations, rotary drilling rigs use picks as tools. The picks rotate with the revolution of the drill bit, causing sliding and breaking the rock under shear conditions. Since the shear strength of rock is much lower than its compressive strength, it is easier to break the rock.
[0005] In terms of materials, the cemented carbide material YG10C used in traditional rotary drilling picks has a grain size of no more than 4μm (according to the ISO 4499 cut-line method), but its thermal fatigue resistance and wear resistance are insufficient. In order to solve these problems, the cemented carbide material of rotary drilling picks has been upgraded to YG8C, with a grain size of 4-7μm (according to the ISO 4499 cut-line method), and its thermal fatigue resistance and wear resistance have been significantly improved. However, when facing hard rock rotary drilling and dry hole rotary drilling conditions above f10, the YG8C material still faces the challenges of insufficient wear resistance and high-temperature plastic deformation. Summary of the invention
[0006] The present invention aims to overcome the defects of the prior art and provide an ultra-coarse cemented carbide.
[0007] Another object of the present invention is to provide a method for preparing the above-mentioned super-coarse cemented carbide.
[0008] Another object of the present invention is to provide an application of the above-mentioned super-coarse cemented carbide.
[0009] The technical solution of the present invention is as follows:
[0010] A super coarse cemented carbide, whose main chemical components are WC and Co, wherein the content of WC is greater than that of Co, the average grain size of WC is 4.0 μm-9.0 μm, the proportion of WC grains below 2 μm is 20%-60%, the proportion of WC grains above 3 times the average grain size is 10%-40%, and the grain size distribution curve of the WC grains presents a coarse grain tailing morphology.
[0011] In a preferred embodiment of the present invention, the chemical composition includes the following components: WC 89.5wt.%-93.9wt.%, Co 6wt.%-10wt.% and other components 0.1wt.%-0.5wt.%, and other components include TaC, NbC and ZrC.
[0012] The technical principle of the preparation method of the ultra-coarse cemented carbide of the present invention is as follows:
[0013] Existing ultra-coarse cemented carbide usually uses tungsten carbide (WC) powder of a single particle size as raw material, and is prepared by post-processing of the ultra-coarse powder and optimizing the wet grinding process. In the cemented carbide obtained by this preparation method, the WC grain size presents a normal distribution. However, in hard rock, dry hole and complex rotary drilling conditions, the alloy with a normal particle size distribution cannot effectively isolate and wrap the WC grains due to the uneven distribution of the bonding phase. In particular, at the WC / WC interface, there is an extremely thin bonding phase, and it is this extremely thin bonding phase that determines the toughness of the alloy. At the same time, the bonding phase area around the WC grains has poor wear resistance and is easily worn during operation. Therefore, the existing ultra-coarse cemented carbide picks are prone to fragmentation and poor wear resistance in hard rock, dry hole and complex rotary drilling conditions.
[0014] To solve this problem, the present invention uses continuously distributed ultra-coarse WC powder and uses it in combination with medium-coarse WC powder. Figure 1 As shown in the figure, the medium-coarse WC powder is dispersed in the gaps of the ultra-coarse WC powder, thereby refining the grains of the cobalt (Co) binder phase. In addition, the continuously distributed ultra-coarse WC grains further increase the thickness of the cobalt layer at the WC / WC junction, thereby significantly improving the strength and toughness of the alloy.
[0015] The preparation method of the above-mentioned super coarse cemented carbide specifically comprises the following steps:
[0016] (1) According to the ratio of the alloy, WC powder, Co powder and forming agent powder are premixed to obtain a premixed powder; wherein the WC powder is composed of medium-coarse WC powder and ultra-coarse WC powder prepared by high-temperature reduction and high-temperature carbonization process in a weight ratio of 65:35-70:30, the medium-coarse WC powder has a supplied particle size of 1.8 μm-2.0 μm, and a ground particle size of 1.2 μm-1.3 μm, and the ultra-coarse WC powder has a supplied particle size of 20 μm-22 μm and a ground particle size of 7.2 μm-7.5 μm;
[0017] (2) ball milling the premixed powder obtained in step (1) to obtain a mixed material;
[0018] (3) The mixed material obtained in step (2) is spray-dried and granulated and low-pressure sintered in sequence to obtain the ultra-coarse cemented carbide.
[0019] In a preferred embodiment of the present invention, in the ball milling of step (2): baseball is added at a ball-to-material ratio of 3:1-4:1, anhydrous ethanol is added at a liquid-to-solid ratio of 0.12-0.15 L / kg, and the ball milling time is 25h-30h.
[0020] In a preferred embodiment of the present invention, the temperature of the low-pressure sintering in step (3) is 1440-1460°C.
[0021] In a preferred embodiment of the present invention, in the ball milling of step (2): baseball is added at a ball-to-material ratio of 3:1-4:1, anhydrous ethanol is added at a liquid-to-solid ratio of 0.12-0.15 L / kg, and the ball milling time is 25h-30h; the temperature of the low-pressure sintering in step (3) is 1440-1460°C.
[0022] The application of the above-mentioned super-coarse cemented carbide in the preparation of rotary drilling picks.
[0023] A rotary drilling pick, the raw material of which is the above-mentioned super-coarse hard alloy.
[0024] A barrel drill is provided with the above-mentioned rotary drilling pick.
[0025] A rotary drilling rig comprises the above-mentioned barrel drill. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 It is a schematic structural diagram of the ultra-coarse cemented carbide of the present invention.
[0027] Figure 2 Schematic diagram of the particle size distribution of the ultra-coarse cemented carbide of the present invention. In which: a is the WC grain size distribution of the ultra-coarse cemented carbide prepared in Example 1 of the present invention, and b is the WC grain size distribution of the YG8C cemented carbide of the conventional comparative example 1.
[0028] Figure 3 This is a photo of the test results of Example 3 of the present invention.
[0029] Figure 4 This is a photo of the test results of Example 4 of the present invention.
[0030] Figure 5 This is a photo of the test results of Example 5 of the present invention.
[0031] Figure 6 The metallographic photographs of the ultra-coarse cemented carbide prepared in Example 1 of the present invention are shown in Figure 1. Among them: a is the metallographic photograph of the ultra-coarse cemented carbide prepared in Example 1 of the present invention, and b is the metallographic photograph of the conventional YG8C cemented carbide for comparison. It can be seen that in the metallographic photograph of the ultra-coarse cemented carbide prepared in Example 1, the fine WC particles are uniformly dispersed and filled in the gaps between the coarse WC particles. In contrast, the WC particle size distribution of the conventional YG8C alloy (Comparative Example 1) is more concentrated, the number of fine WC particles is small, and the distribution is irregular. DETAILED DESCRIPTION
[0032] The technical solution of the present invention is further illustrated and described below through specific implementation modes in combination with the accompanying drawings.
[0033] Example 1
[0034] (1) According to the composition ratio of YG8C alloy (Co content 8wt.%, the total content of TaC, NbC and ZrC is not higher than 0.03wt.%, and the balance is WC), WC powder, Co powder and paraffin molding agent powder are simultaneously charged into a double cone mixer for premixing for at least 3 hours to obtain a premixed powder; wherein the WC powder is composed of medium-coarse WC powder and ultra-coarse WC powder prepared by high-temperature reduction and high-temperature carbonization process in a weight ratio of 65:35, the medium-coarse WC powder has a supplied particle size of 2.0μm and a ground particle size of 1.3μm, and the ultra-coarse WC powder has a supplied particle size of 22μm and a ground particle size of 7.5μm;
[0035] (2) adding the premixed powder obtained in step (1) into a ball mill for ball milling to obtain a mixed material, wherein in the ball milling of this step: baseball is added at a ball-to-material ratio of 3:1, anhydrous ethanol is added at a liquid-to-solid ratio of 0.12 L / kg, and the ball milling time is 25 h;
[0036] (3) After the mixed material obtained in step (2) is discharged, spray drying and granulation and low-pressure sintering at 1450° C. are performed in sequence to obtain Figure 6 The super coarse cemented carbide shown in a has an average grain size of WC of 5.0 μm, WC grains with a grain size of less than 2 μm account for 45%, and WC grains with a grain size of more than 3 times the average grain size account for 30%; Figure 2As shown in a, the particle size distribution curve of the WC grains presents a coarse-grained tailing morphology, and there is no obvious double-peak structure on the particle size frequency distribution curve of WC. Double peaks refer to two peaks on the particle size distribution curve, indicating that there are two particle sizes with a high proportion in the particle size distribution.
[0037] Example 2
[0038] (1) According to the composition ratio of YG6C alloy (Co content 8wt.%, TaC content 0.3wt.%, the rest is WC). WC powder, Co powder, TaC powder and paraffin molding agent powder are simultaneously loaded into a double cone mixer for premixing for at least 5 hours to obtain a premixed powder; wherein the WC powder is composed of medium-coarse WC powder and ultra-coarse WC powder prepared by high-temperature reduction and high-temperature carbonization process in a weight ratio of 70:30, and the medium-coarse WC powder has a supplied particle size of 1.8μm and a ground particle size of 1.2μm. The ultra-coarse WC powder has a supplied particle size of 20μm and a ground particle size of 7.2μm;
[0039] (2) adding the premixed powder obtained in step (1) into a ball mill for ball milling to obtain a mixed material, wherein in the ball milling of this step: baseball is added at a ball-to-material ratio of 4:1, anhydrous ethanol is added at a liquid-to-solid ratio of 0.15 L / kg, and the ball milling time is 28 h;
[0040] (3) After the mixed material obtained in step (2) is unloaded, spray drying and granulation and low-pressure sintering at 1450° C. are carried out in sequence to obtain the ultra-coarse cemented carbide, wherein the average grain size of WC is 6.0 μm, the proportion of WC grains with a grain size of less than 2 μm is 35%, the proportion of WC grains with a grain size of more than 3 times the average grain size is 30%, and the particle size distribution curve of the WC grains presents a coarse grain tailing morphology.
[0041] Comparative Example 1
[0042] (1) According to the composition ratio of YG8C alloy, the Co content is 8.0wt.%, the content of other carbides (TaC, NbC and ZrC) does not exceed 0.03wt.%, and the balance is WC. The ultra-coarse WC powder of 22μm as supplied, the cobalt powder and the paraffin powder are simultaneously charged into a ball mill for ball milling to obtain a mixed material. In the ball milling of this step: baseball is added at a ball-to-material ratio of 3:1, anhydrous ethanol is added at a liquid-to-solid ratio of 0.12L / kg, and the ball milling time is 25h;
[0043] (2) After the mixed material obtained in step (1) is discharged, spray drying and granulation and low-pressure sintering at 1450° C. are performed in sequence to obtain Figure 6 b shows the YG8C alloy, in which the average grain size of WC is 6.0 μm, the WC particles with a grain size of less than 2 μm account for about 8%, the number of WC grains with a grain size of three times the average grain size accounts for 5%, and the WC grain size is concentrated (such as Figure 2b).
[0044] Example 3
[0045] The rock formations of the pile foundation of Anhe Expressway are mainly medium-weathered limestone, and the hardness of the rock formations is about 80-100MPa. The pile hole has a diameter of 1.8m and a depth of 32m. A 1.2m diameter barrel drill is used to test the performance of the pick made of ultra-coarse cemented carbide in Example 1 of the present invention. The testing equipment is XCMG XR400E, and the rotary drilling barrel can hold a total of 10 picks. During the test, the rotary drilling barrel is installed with picks made of ultra-coarse cemented carbide in Example 1 and comparison picks (conventional YG8C) at intervals, and the number of pick consumption is compared under the same number of drilling meters. Figure 3 As shown, the test results show that the number of picks consumed per hole made of the ultra-coarse cemented carbide in Example 1 is reduced by about 40% compared with the picks made of conventional YG8C (Comparative Example 1).
[0046] Example 4
[0047] The rock formation of the pile foundation of Guiyang Big Data Science and Technology City is medium-weathered dolomite with a hardness of 80-100MPa. The pile hole has a diameter of 1.8m and a depth of 15m. A 1.5m diameter barrel drill is used to test the performance of the YG8C alloy pick made of ultra-coarse cemented carbide in Example 1 of the present invention. The testing equipment is XCMG XR460E, and the rotary drilling barrel can hold a total of 10 picks. During the test, the rotary drilling barrel is installed with picks made of ultra-coarse cemented carbide in Example 1 and comparison picks (conventional YG8C) at intervals, and the number of pick consumption is compared under the same number of drilling meters. Figure 4 As shown, the test results show that the number of picks consumed per hole made of the ultra-coarse cemented carbide in Example 1 is reduced by about 50% compared with the picks made of conventional YG8C (Comparative Example 1).
[0048] Example 5
[0049] The rock formation of the pile foundation of Wudan to Tianshan Expressway is medium-weathered granite with a hardness of 80-120MPa. The pile hole has a diameter of 1.2m and a depth of 26m. A 1.2m diameter barrel drill is used to test the performance of the YG6C alloy pick made of ultra-coarse cemented carbide in Example 2 of the present invention. The testing equipment is Sany Heavy Industry SR405R, and the rotary drilling barrel can hold a total of 10 picks. During the test, the rotary drilling barrel is installed with picks made of ultra-coarse cemented carbide in Example 2 and comparison picks (conventional YG6C) at intervals, and the number of picks consumed is compared under the same number of drilling meters. Figure 5 As shown, the test results show that the number of picks consumed per hole of the pick made of the super-coarse cemented carbide in Example 2 is reduced by about 30% compared with the picks made of conventional YG6C (purchased from existing commercial channels).
[0050] The above description is only a preferred embodiment of the present invention, and therefore cannot be used to limit the scope of the present invention. That is, equivalent changes and modifications made according to the patent scope of the present invention and the contents of the specification should still fall within the scope of the present invention.
Claims
1. An ultra-coarse cemented carbide, characterized in that: The main chemical components are WC and Co, the content of WC is greater than that of Co, the average grain size of WC is 4.0μm-9.0μm, the WC grains with a grain size below 2μm account for 20%-60%, the WC grains with a grain size of more than 3 times the average grain size account for 10%-40%, and the grain size distribution curve of the WC grains presents a coarse-grained tailing morphology.
2. The super-coarse cemented carbide according to claim 1, characterized in that: Its chemical composition includes the following components: WC 89.5wt.%-93.9wt.%, Co 6wt.%-10wt.% and other components 0.1wt.%-0.5wt.%, and other components include TaC, NbC and ZrC.
3. The method for preparing the ultra-coarse cemented carbide according to claim 1 or 2, characterized in that: The steps include: (1) According to the ratio of the alloy, WC powder, Co powder and forming agent powder are premixed to obtain a premixed powder; wherein the WC powder is composed of medium-coarse WC powder and ultra-coarse WC powder in a weight ratio of 65:35-70:30, the medium-coarse WC powder has a supplied particle size of 1.8 μm-2.0 μm and a ground particle size of 1.2 μm-1.3 μm, and the ultra-coarse WC powder has a supplied particle size of 20 μm-22 μm and a ground particle size of 7.2 μm-7.5 μm; (2) ball milling the premixed powder obtained in step (1) to obtain a mixed material; (3) The mixed material obtained in step (2) is spray-dried and granulated and low-pressure sintered in sequence to obtain the ultra-coarse cemented carbide.
4. The preparation method according to claim 3, characterized in that: In the ball milling of step (2), baseballs are added at a ball-to-material ratio of 3:1-4:1, anhydrous ethanol is added at a liquid-to-solid ratio of 0.12 L / kg-0.15 L / kg, and the ball milling time is 25 h-30 h.
5. The preparation method according to claim 3, characterized in that: The temperature of the low-pressure sintering in step (3) is 1440-1460°C.
6. The preparation method according to claim 3, characterized in that: In the ball milling of step (2), baseballs are added at a ball-to-material ratio of 3:1-4:1, anhydrous ethanol is added at a liquid-to-solid ratio of 0.12L / kg-0.15L / kg, and the ball milling time is 25h-30h; the low-pressure sintering temperature of step (3) is 1440°C-1460°C.
7. Use of the super-coarse cemented carbide according to claim 1 or 2 in the preparation of rotary drilling picks.
8. A rotary drilling pick, characterized in that: The raw material thereof comprises the super coarse cemented carbide as claimed in claim 1 or 2.
9. A barrel drill, characterized in that: A rotary drilling pick as claimed in claim 8.
10. A rotary drilling rig, characterized in that: A barrel drill according to claim 9.
Citation Information
Patent Citations
Hard alloy for spherical tooth drill bit suitable for welding processing
CN101880809A
Preparation method of ultra-coarse grain WC-Co hard alloy
CN106636837A
Preparation method of extra-coarse grain WC-Co hard alloy
CN110387497A
Gradient-structure cemented carbide button and preparation method thereof
CN111069610A
Hard alloy with non-uniform structure as well as preparation method and application of hard alloy
CN114277300A